1997
DOI: 10.1074/jbc.272.35.21892
|View full text |Cite
|
Sign up to set email alerts
|

Dimer to Monomer Conversion of the Cytochromeb6 f Complex

Abstract: The molecular weight of the cytochrome b 6 f complex purified from Chlamydomonas reinhardtii thylakoid membranes has been determined by combining velocity sedimentation measurements, molecular sieving analyses, and determination of its lipid and detergent content. The complex in its enzymatically active form is a dimer. Upon incubation in detergent solution, it converts irreversibly into an inactive, monomeric form that has lost the Rieske iron-sulfur protein, the b 6 f-associated chlorophyll, and, under certa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
174
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 139 publications
(183 citation statements)
references
References 70 publications
7
174
2
Order By: Relevance
“…The latter function for the long chain ␤-carotene and the Chl a with its long phytyl chain is suggested by the role for ␤-carotene in stabilization of the assembly of the D1 protein into a functional photosystem II complex (31) and of the LHCI polypeptides (35) and, as well, the proposal that bound chlorophyll a prevents dissociation of the cytochrome b 6 f dimer into monomers (12).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The latter function for the long chain ␤-carotene and the Chl a with its long phytyl chain is suggested by the role for ␤-carotene in stabilization of the assembly of the D1 protein into a functional photosystem II complex (31) and of the LHCI polypeptides (35) and, as well, the proposal that bound chlorophyll a prevents dissociation of the cytochrome b 6 f dimer into monomers (12).…”
Section: Discussionmentioning
confidence: 99%
“…PCC 6803 (36). From the precedents of loss of chlorophyll upon monomerization or dissociation of the Rieske protein (12) and of diminished content of ␤-carotene in the C. reinhardtii complex (Table I), it is possible that the measurements of triplet transfer to ␤-carotene in Peterman et al (36) were made difficult by a lowered content of ␤-carotene and chlorophyll a that is a consequence of the loss of the Rieske protein in this preparation, which results in complete loss of activity. Preliminary experiments designed to detect by EPR the presence of a ␤-carotene triplet in the b 6 f complex following laser excitation of the chlorophyll a did not reveal any component that could be unambiguously assigned to a carotenoid triplet with a decay time in the expected 0.5-10 s time range.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3, where it appears that FCCP did not alter either the oligomeric state cytochrome b 6 f complex nor its composition. The treated complex migrated as a dimer (36), and all subunits comigrated, especially the Rieske protein. This is important evidence for the structural integrity of the complex, as it has been shown that in case of any perturbation of the complex, the Rieske protein is the first subunit to be lost (4,33,36).…”
Section: Effects Of Increasing Concentrations Of Fccp On the Cytochromentioning
confidence: 99%
“…Briefly, specific solubilization of the thylakoid membranes by 6-O-(N-heptylcarbamoyl)-methyl-␣-d-glycopyranoside (Hecameg) 2 is followed by sucrose gradient and hydroxylapatite chromatography. The two last steps of purification must be performed in the presence of lipids (egg L-␣-phosphatidylcholine (PC)) and at the critical micellar concentration of the detergent to prevent dissociation of the complex (38).…”
Section: Methodsmentioning
confidence: 99%